2002
DOI: 10.4049/jimmunol.168.11.5885
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA Encoding IFN-γ-Inducible Protein 10 Redirects Antigen-Specific T Cell Polarization and Suppresses Experimental Autoimmune Encephalomyelitis

Abstract: IFN-γ-inducible protein 10 (IP-10) is a CXC chemokine that stimulates the directional migration of activated T cells, particularly Th1 cells. We demonstrate in this work that during activation this chemokine drives naive CD4+ T cells into Th1 polarization. Administration of plasmid DNA encoding self IP-10 was found capable of breaking down immunological tolerance to IP-10, resulting in the generation of self-specific immunity to the gene product of the vaccine. Despite the CpG motif that drives T cells into Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 46 publications
6
95
0
Order By: Relevance
“…Gene therapy has not yet been attempted in MS, but there have been a number of studies in EAE that have invariably shown some level of efficacy at inhibiting the disease (Table 1), although in many cases this has only been an amelioration rather than elimination of disease. As the majority of the CNS is postmitotic, this puts constraints on the nature of the vector that can be used, and to date administration of plasmid DNA, [32][33][34][35][36][37][38][39][40][41] viral infection, [42][43][44][45][46][47][48][49][50][51][52][53] and retrovirally transduced cell (RVC)-carriers 47,[54][55][56][57][58][59][60][61][62][63] have been investigated in EAE (Table 1). These have largely focused on inhibition of the immune response either applied centrally to target the local pathological events within the CNS or peripherally administered to inhibit: initial sensitization, the activities of circulating cells or perivascular events in areas of local BBB breakdown.…”
Section: Gene Therapy In Autoimmune Demyelinating Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Gene therapy has not yet been attempted in MS, but there have been a number of studies in EAE that have invariably shown some level of efficacy at inhibiting the disease (Table 1), although in many cases this has only been an amelioration rather than elimination of disease. As the majority of the CNS is postmitotic, this puts constraints on the nature of the vector that can be used, and to date administration of plasmid DNA, [32][33][34][35][36][37][38][39][40][41] viral infection, [42][43][44][45][46][47][48][49][50][51][52][53] and retrovirally transduced cell (RVC)-carriers 47,[54][55][56][57][58][59][60][61][62][63] have been investigated in EAE (Table 1). These have largely focused on inhibition of the immune response either applied centrally to target the local pathological events within the CNS or peripherally administered to inhibit: initial sensitization, the activities of circulating cells or perivascular events in areas of local BBB breakdown.…”
Section: Gene Therapy In Autoimmune Demyelinating Diseasementioning
confidence: 99%
“…Injection of plasmid DNA exhibits poor transduction efficiencies and when used successfully, this has used multiple injections often in regenerating (muscle) tissue. 32,33,[35][36][37][38][39][40] The regulatory sequences of plasmid DNA is important for efficacy 40 and these (eg CG repeats) can modulate cytokine production in vivo and can either suppress or worsen EAE, probably because of a secondary effect on sensitization. 69,70 As an alternative approach to achieving local CNS delivery, the migratory potential of primed T lymphocytes has been harnessed and thus allows for systemic delivery.…”
Section: Systemic Immunogene Therapy In Cns Autoimmunitymentioning
confidence: 99%
“…10 The vaccination approach has been effective in the generation of selfantibodies against plasmid-encoded chemokine antigens (including MCP-1, MIP-1a, and RANTES) with therapeutic effect in experimental adjuvant arthritis; 11 in similar studies in an experimental autoimmune encephalomyelitis (EAE) model, the encoded antigen was the chemokine IP-10. 12 In NZB/NZW F1 lupus-prone mice, vaccination with plasmid DNA encoding MHC class I epitopes of the heavy chain variable region of anti-DNA antibodies induced cytotoxic T lymphocytes (CTL) that killed autoreactive B cells. 13 The vaccination approach could potentially be further developed so that plasmid DNA encoding autoimmune antigens trigger the development of tolerance and reversal of the underlying cause of an autoimmune disease.…”
Section: Naked Dnamentioning
confidence: 99%
“…The vaccines decreased the number of relapses in acute EAE and prevented epitope spreading. It is worth noting that some caution may be needed with respect to the application of tolerizing DNA vaccines to the treatment of multiple sclerosis as both beneficial and detrimental outcomes have been reported in EAE [29,[86][87][88][89][90][91]. Similarly, a lipid microarray which included gangliosides, sulfatide cerebroside, and sphingomyelin was produced for the study of lipid-specific antibodies in the CSF of individuals with relapsing-remitting and secondary progressive multiple sclerosis and sera derived from acute EAE in the mouse [92].…”
Section: Profiling Of the Autoantibody Response In Multiple Sclerosismentioning
confidence: 99%